Identification and characterization of the LDAP family revealed GhLDAP2_Dt enhances drought tolerance in cotton - Zhao, Yanyan; Duan, Bailin; Liu, Yuxin; Wu, Yuqing; Yu, Dongliang; Ke, Liping; Cai, Fangfang; Mei, Jun; Zhu, Ning; Sun, Yuqiang (Frontiers in Plant Science, 2023)
Lipid droplet-associated proteins (LDAPs) play essential roles in tissue growth and development and in drought stress responses in plants. Cotton is an important fiber and cash crop; however, the LDAP family has not been characterized in cotton. In this study, a total of 14, six, seven, and seven genes were confirmed as LDAP family members in Gossypium hirsutum, Gossypium raimondii, Gossypium arboreum, and Gossypium stocksii, respectively. Additionally, expansion in the LDAP family occurred with the formation of Gossypium, which is mirrored in the number of LDAPs found in five Malvaceae species (Gossypioides kirkii, Bombax ceiba, Durio zibethinus, Theobroma cacao, and Corchorus capsularis), Arabidopsis thaliana, and Carica papaya. The phylogenetic tree showed that the LDAP genes in cotton can be divided into three groups (I, II, and III). The analysis of gene structure and conserved domains showed that LDAPs derived from group I (LDAP1/2/3) are highly conserved during evolution, while members from groups II and III had large variations in both domains and gene structures. The gene expression pattern analysis of LDAP genes showed that they are expressed not only in the reproductive organs (ovule) but also in vegetative organs (root, stem, and leaves). The expression level of two genes in group III, GhLDAP6_At/Dt, were significantly higher in fiber development than in other tissues, indicating that it may be an important regulator of cotton fiber development. In group III, GhLDAP2_At/Dt, especially GhLDAP2_Dt was strongly induced by various abiotic stresses. Decreasing the expression of GhLDAP2_Dt in cotton via virus-induced gene silencing increased the drought sensitivity, and the over-expression of GhLDAP2_Dt led to increased tolerance to mannitol-simulated osmotic stress at the germination stage. Thus, we conclude that GhLDAP2_Dt plays a positive role in drought tolerance.